2008
DOI: 10.1063/1.2812555
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamics of the H++D2(v=,j=)→HD+D+ reaction: A comparison between theory and experiment

Abstract: The H++D2(v=0,j=0)→HD+D+ reaction has been theoretically investigated by means of a time independent exact quantum mechanical approach, a quantum wave packet calculation within an adiabatic centrifugal sudden approximation, a statistical quantum model, and a quasiclassical trajectory calculation. Besides reaction probabilities as a function of collision energy at different values of the total angular momentum, J, special emphasis has been made at two specific collision energies, 0.1 and 0.524eV. The occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
99
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(115 citation statements)
references
References 53 publications
13
99
1
2
Order By: Relevance
“…Motivated for this experimental work, comparisons with theoretical results obtained in exact quantum mechanical ͑EQM͒ ͑that is, fully converged close coupling͒ and quasiclassical trajectory ͑QCT͒ calculations were soon reported. 3,[5][6][7] QCT angular distributions were found to be more symmetric about the sideway scattering direction ͑ ϳ 90°͒ than the corresponding experimental result at a collision energy of E c = 0.524 eV. 3 Hayes and Skodje 6 showed that at least part of the apparent slight asymmetry of the measured DCS could be attributed to an attenuation of the TOF signal as a function of the scattering angle due to the finite lifetime of the Rydberg state.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Motivated for this experimental work, comparisons with theoretical results obtained in exact quantum mechanical ͑EQM͒ ͑that is, fully converged close coupling͒ and quasiclassical trajectory ͑QCT͒ calculations were soon reported. 3,[5][6][7] QCT angular distributions were found to be more symmetric about the sideway scattering direction ͑ ϳ 90°͒ than the corresponding experimental result at a collision energy of E c = 0.524 eV. 3 Hayes and Skodje 6 showed that at least part of the apparent slight asymmetry of the measured DCS could be attributed to an attenuation of the TOF signal as a function of the scattering angle due to the finite lifetime of the Rydberg state.…”
Section: Introductionmentioning
confidence: 97%
“…Recent experimental studies by means of the Rydberg H-atom translational spectroscopy technique 1 have enabled the analysis of translational energy distributions, time-of-flight ͑TOF͒ spectra, differential cross sections ͑DCSs͒, and relative rotational populations for the H ‫ء‬ ͑n͒ +D 2 reaction, [2][3][4][5] where H ‫ء‬ ͑n͒ corresponds to a highly excited Rydberg H atom. Due to this high excitation, H͑n ϳ 35͒, the Rydberg excited H atom behaves in practice as an ion, H + , during the collision with D 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The application of different statistical techniques has provided good estimates of both quantum mechanical (QM) calculations and experimental work performed on the system. Thus, for instance, most of the information inferred from Rydberg H-atom time-offlight spectroscopic measurements [27][28][29] have been successfully reproduced 30,31 by means of a statistical quantum mechanical (SQM) method. 32,33 Different alternative approaches based on the assumption of the formation of an intermediate complex with a long enough lifetime before its fragmentation proved adequate to describe the dynamics of the process.…”
Section: Introductionmentioning
confidence: 99%
“…These two approaches have been applied in common for a better understanding of the dynamics of several atomdiatom reactions such as N+H 2 , 53 O+OH, 54 H + +H 2 , 4,55,56 and H + +D 2 . 14,31 Numerical details of the TIQM calculation performed by Honvault and Scribano were given before. 49 The number of rovibrational states for the reactant and product channels and of helicity components was found to guarantee converged results down to energies within the 10 −4 eV-10 −3 eV range.…”
Section: Theorymentioning
confidence: 99%
“…At energies below ≈1.7 eV, the proton exchange is the only reactive channel, and the process can be described on the ground adiabatic PES [19][20][21][22]. Since the PES is characterized by a deep well or complex (≈4.5 eV), as illustrated in Fig.…”
mentioning
confidence: 99%